2014
DOI: 10.1016/j.molcel.2014.02.034
|View full text |Cite
|
Sign up to set email alerts
|

A Regulatory Signaling Loop Comprising the PGAM5 Phosphatase and CK2 Controls Receptor-Mediated Mitophagy

Abstract: Mitochondrial autophagy, or mitophagy, is a major mechanism involved in mitochondrial quality control via selectively removing damaged or unwanted mitochondria. Interactions between LC3 and mitophagy receptors such as FUNDC1, which harbors an LC3-interacting region (LIR), are essential for this selective process. However, how mitochondrial stresses are sensed to activate receptor-mediated mitophagy remains poorly defined. Here, we identify that the mitochondrially localized PGAM5 phosphatase interacts with and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
419
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 466 publications
(432 citation statements)
references
References 57 publications
12
419
0
1
Order By: Relevance
“…39 Indeed, phosphatases have recently been linked to the autophagy pathway, such as several well-known phosphatases (PTEN, PPM1D/WIP1, PTPRS/PTPs, and PPP2CA), and newly identified phosphatases (PGAM5, SGPP1 [sphingosine-1-phosphate phosphatase 1] and calcineurin). 20,[40][41][42][43] However, none of these studies have directly linked the activity of phosphatases to ATG16L1 function. This study not only identified PPP1 as a phosphatase that directly dephosphorylates CSNK2-phosphorylated ATG16Ll, but also indicated that ATG16Ll binds to PPP1 Experiments were repeated at least 3 times.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Indeed, phosphatases have recently been linked to the autophagy pathway, such as several well-known phosphatases (PTEN, PPM1D/WIP1, PTPRS/PTPs, and PPP2CA), and newly identified phosphatases (PGAM5, SGPP1 [sphingosine-1-phosphate phosphatase 1] and calcineurin). 20,[40][41][42][43] However, none of these studies have directly linked the activity of phosphatases to ATG16L1 function. This study not only identified PPP1 as a phosphatase that directly dephosphorylates CSNK2-phosphorylated ATG16Ll, but also indicated that ATG16Ll binds to PPP1 Experiments were repeated at least 3 times.…”
Section: Discussionmentioning
confidence: 99%
“…The mammalian CSNK2 is heterotetrameric form consisting of 2 catalytic subunits (CSNK2A1 and CSNK2A2) and 2 regulatory subunits www.tandfonline.com(CSNK2B). Our in vitro kinase assay showed that both of the CSNK2 catalytic subunits (CSNK2A1 and CSNK2A2), but not the kinase-dead mutants CSNK2A1 K68M and CSNK2A2 K69M , 20 can phosphorylate ATG16L1 ( Fig. 2C and D).…”
Section: Csnk2 Was Responsible For Atg16l1 Phosphorylation In H/rtreamentioning
confidence: 92%
“…Mitochondrial protein PGAM5 functions in multiple cell death pathways [35] and regulates mitophagic protection against cell necroptosis [36]. PGAM5 catalyses the dephosphorylation of FUNDC1 which enhances its interaction with microtubule-associated protein 1A/1B-light chain 3, leading to mitophagy [37]. PGAM5 also promotes inflammasome activation in macrophages [38].…”
Section: Discussionmentioning
confidence: 99%
“…FUNDC1-mediated mitophagy is regulated at the posttranslational level by reversible phosphorylation. Under normal physiological conditions FUNDC1 is phosphorylated by Src kinase at Tyr18, which is located in the LIR motif, and at Ser13 by CK2 ( Figure 3C) (Chen et al, 2014a). In response to hypoxia or loss of mitochondrial membrane potential the mitochondrially localized phosphoglycerate mutase family member 5 (PGAM5), a Ser/Thr phosphatase, dephosphorylates FUNDC1 at Ser13, whereas Tyr18 phosphorylation seems to be prevented before mitophagyinduction due to inactivation of Src kinase ( Figure 3C) (Chen et al, 2014a).…”
Section: Hif-dependent Regulation Of Mitophagymentioning
confidence: 99%